Effect of microwave sintering on the properties of copper oxide doped alumina toughened zirconia (ATZ) - M.K.G. Abbas; S. Ramesh; S.F.H. Tasfy; K.Y. Sara Lee (Journal of Materials Research and Technology, 2023)
This study investigated the effect of copper oxide addition on the alumina toughened zirconia composite ceramic using microwave sintering. CuO amounts (0.05–1 wt%) were examined at sintering temperatures (1250–1500 °C). Investigations covered hardness, toughness, phase stability, microstructure, and densification. Optimum doping was 0.2 wt%, resulting in a composite with 99% relative density at 1500 °C, Vickers hardness of 13.1 GPa, and fracture toughness of 7.1 MPa m1/2. Low-temperature degradation showed disrupted phase stability above 1400 °C, with CuO unable to prevent ageing-induced phase transformation.